Optimal Policies for Solid Waste Disposal: Taxes, Subsidies and Standards - Palmer, Karen; Walls, Margaret (School of Management Working Papers, 1996)
Pricing trash collection and disposal services can be politically unpopular and may lead to increased illegal disposal of trash. Several studies have shown that deposit-refund systems can act like disposal charges without the illegal disposal problem and thus can generate an optimal amount of solid waste disposal. We assess the efficiency implications of an alternative policy currently in use in some states and considered at the federal level, recycled content standards. These are requirements that a certain fraction of total input use be comprised of secondary materials. We find that such standards by themselves cannot generate the optimal amount of disposal but must be combined with additional taxes on both the final product and other inputs to production. Moreover, the information requirements for setting the optimal standards and accompanying taxes are high. The deposit-refund approach would be preferred in most cases.